Arthroscopic micro fracture and intra articular whole bone marrow injection for the treatment of articular cartilage lesions in the knee joint. - Alobidi, Firas A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Articular cartilage lesions in the knee joint are frequently seen,its treatment represents a challenge for orthopedic surgeons especially in young age patients and if left untreated,then they can progress to advanced osteoarthritis that may affect the functional status of the patients.Many treatment modalities had developed for these lesions, in the current study arthroscopic micro fracture plus intra articular whole bone marrow(WBM) injection was used as modality of treating these lesions. Objectives: to assess the effectiveness of arthroscopic micro fracture plus WBM intra articular injection as a treatment modality for knee articular cartilage lesions. Patients and Methods : a prospective experimental study was performed on 30 patients (14 females,16 males ) with a mean age of 38.6 years who had chondral lesions in their knee joint that failed to respond to conservative treatment.Arthroscopic micro fracture plus WBM intra articular injection was done to them.The functional assessment of the patients and their knee pain were evaluated by modified Cincinnati knee rating score (CKRS) and Visual Analogue Scale (VAS) respectively, both preoperatively and six months postoperatively. These results were compared. Results: there was statistically significant improvement in a modified CKRS and VAS six months after surgery.26 patients out of 30 patients (86.7 %) were improved. The improvement was statistically significant for those patients ≤ 40 years of age and also for those above 40 yeas of age, but it was more pronounced in those patients ≤ 40 years. Conclusion : Arthroscopic micro fracture plus intra articular WBM injection is an effective treatment modality for small,well defined,full thickness chondral lesions in the knee joint especially for those ≤ 40 years old on short term follow up. A long term follow up is needed.